A systematic review of interventions to prevent suicidal behaviors and reduce suicidal ideation in older people. (2nd August 2017) - Okolie, Chukwudi; Dennis, Michael; Simon Thomas, Emily; John, Ann
ABSTRACT: Background: Older people have a high risk of suicide but research in this area has been largely neglected. Unlike for younger age groups, it remains unclear what strategies for prevention exist for older adults. This systematic review assesses the effectiveness of interventions to prevent suicidal behavior and reduce suicidal ideation in this age group. Methods: MEDLINE, EMBASE, PsycINFO, Web of Science, and Cochrane Central Register of Controlled Trials (CENTRAL) were searched for relevant publications from their dates of inception until 1 April 2016. Studies included in this review report effectiveness data about interventions delivered to older adults to prevent suicidal behavior (suicide, attempted suicide, and self-harm without suicidal intent) or reduce suicidal ideation. A narrative synthesis approach was used to analyze data and present findings. Results: Twenty one studies met the criteria for inclusion in the study. Most programs addressed risk predictors, specifically depression. Effective interventions were multifaceted primary care-based depression screening and management programs; treatment interventions (pharmacotherapy and psychotherapy); telephone counseling for vulnerable older adults; and community-based programs incorporating education, gatekeeper training, depression screening, group activities, and referral for treatment. Most of the studies were of low quality apart from the primary care-based randomized controlled trials. Conclusions: Multifaceted interventions directed at primary care physicians and populations, and at-risk elderly individuals in the community may be effective at preventing suicidal behavior and reducing suicidal ideation in older adults. However, more high quality trials are needed to demonstrate successful interventions.